2010
DOI: 10.1111/j.1559-1816.2010.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Do the “Savage Origins” of Tattoos Cast a Prejudicial Shadow on Contemporary Tattooed Individuals?

Abstract: We investigated whether increases in tattooing rates and designs have eradicated or altered traditional delinquent tattooing stereotypes. We tested the perceived suitability of tattooed and non‐tattooed individuals for 2 different jobs. Affective evaluations mediated judgments of job suitability, with those displaying traditional tattoos being rated as less suitable for employment than those who were not tattooed and those displaying contemporary tattoos. Those with a contemporary tattoo were judged in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
6
30
0
Order By: Relevance
“…A great deal of research in the field of Human Resource Management, Industrial-Organizational Psychology and Social Psychology has focused on the impact that tattoos have in the employment arena when it comes to bias, stigma, prejudice, visual cues, social class, recruitment, taste-based discrimination, and/or attitudes (Burgess & Clark, 2010;Larson, Patterson & Markham, 2014;Mendez, 2016;Miller, Nicols & Eure, 2009;Seiter & Hatch, 2005;Swanger, 2006;Totten, Lipscomb, & Jones 2009). One area of tattoo research with limited literature includes what extent does a neck and/or face tattoo have on the Employment Screening Process (ESP) (Timming, Nickson, Re, & Perrett, 2017;Zestcott, Bean, & Stone, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of research in the field of Human Resource Management, Industrial-Organizational Psychology and Social Psychology has focused on the impact that tattoos have in the employment arena when it comes to bias, stigma, prejudice, visual cues, social class, recruitment, taste-based discrimination, and/or attitudes (Burgess & Clark, 2010;Larson, Patterson & Markham, 2014;Mendez, 2016;Miller, Nicols & Eure, 2009;Seiter & Hatch, 2005;Swanger, 2006;Totten, Lipscomb, & Jones 2009). One area of tattoo research with limited literature includes what extent does a neck and/or face tattoo have on the Employment Screening Process (ESP) (Timming, Nickson, Re, & Perrett, 2017;Zestcott, Bean, & Stone, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Face and neck tattoos are challenging at best to cover up during an employment interview; this may result in the interviewer seeing the face or neck tattoo compared to a tattoo located on the upper arm that can be covered up with a dress shirt, leading to the tattoo being hidden from view during the Employment Screening Process (ESP).In their study, Dillingh, Kooreman, and Johannes (2016) reported that 7.4% of the participants reported having a tattoo on the head/face and 2.3% of participants reported that they had a tattoo on the neck area (n=512). Ellis (2015) and other researchers have suggested that exposed tattoos can negatively influence the ESP (Burgess & Clark, 2010). Whorton (2015) acknowledged that exposed tattoos coupled with the employment screener"s personal bias or stigma may result in a negative evaluation of the candidate.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the literature on tattoo perception, Burgess and Clark[ 33 ] have noted that most tattoo perception studies to date have failed take into account the type of tattoo a participant possessed. This is an important omission that has likely contributed to generalizations about tattoos that are misleading in current society, where tattoos of all sizes, locations, and thematic imagery can be found.…”
Section: How Do Others Perceive Those With Tattoos?mentioning
confidence: 99%
“…Tattoos can range from those that are concealed or visible only in more casual or intimate settings to prominent markings on the face, neck, and extremities. Designs can range from “small, trendy, and fun”[ 33 ] fashion accessories to more complex tattoos displaying more provocative or sexual themes covering large portions of the wearer’s body. Intuitively, such widely varying differences in tattoos are expected to be salient in terms of impacting the perceptions of others.…”
Section: How Do Others Perceive Those With Tattoos?mentioning
confidence: 99%
“…prisoners, gang members; Atkinson, 2003). Recently, Burgess and Clark (2010) used such literature as a basis for examining whether the content of a tattoo makes a difference in how tattooed individuals are perceived. In their research, they found that individuals with traditional tattoos were rated less suitable for employment than those displaying contemporary tattoos.…”
Section: Tattooing Todaymentioning
confidence: 99%